The use of tests in guidance work - Limcaco, Esperanza R. (Education quarterly.)
This paper presented five of the more common types of tests used in guidance work and their uses. Prospective students, on the basis of test scores can come to a better understanding of their strengths, their weaknesses, their potentialities and the problems they are most likely to encounter if and when they enter college or the Univer sity of the Philippines. Tests can be the most important single factor in guiding the academic and vocational future of our Filipino youth.